The Effect of Wordwall to the Quality of Students' Writing Skills - Fadilah Putri, Nike; Huda, Tanzil; Devanti, Yeni Mardiyana (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2024)
The aim of the current study was to investigate the effectiveness of the use of Wordwall on the quality of students’ EFL writing skills. Wordwall, a web-based application, is one of the AI-based applications that is used to facilitate teaching-learning activities. It can help students in improving their writing skills, which is essential for EFL skills mastery. However, a lot of students had difficulty in attaining the skill because of some factors such as a lack of vocabulary and other grammar competencies. The data sources were from the result of the score in narrative fractured text made by students in Sekolah Menengah Atas (Senior High School). The method employed in this study was quantitative with an ex post facto design. The measurement of writing test as the data was measured using several criteria followed by a component of writing adapted from Heaton (1988) in Fitriani, et al. (2014). The components of writing skills consisted of content, organization, vocabulary, grammar, and mechanics. The result of this investigation indicated that a class taught along with Wordwall attained an average score of 16.17. Meanwhile, the average value for a class taught using a printed English textbook was 14.43. The results of the independent t-test had a significant difference of 0.000, which meant that it was significantly less than < 0.05. It revealed that the null hypothesis was disregarded, which implied that there was a significant variation in values of the class with used Wordwall (AI) and that without using the AI-based application, i.e., Wordwall. Therefore, it could be concluded that the students’ EFL writing skills who learned English by using Wordwall were better than those of printed English textbooks.